THE DECLINE OF TRADITIONAL LIVESTOCK FARMING IN SPAIN AND ITS IMPACT ON ECOSYSTEM SERVICES: UNDERSTANDING THE DYNAMICS THROUGH FOCUS GROUPS WITH SHEPHERDS - Menor de Gaspar López, Rodrigo; Carrasco Monteagudo, Inmaculada; Gómez Borja, Miguel Ángel (Applied Studies in Agribusiness and Commerce, 2025)
Traditional extensive livestock farming has emerged as a potential sustainable development strategy in Europe, particularly to address rural depopulation and provide multiple positive externalities. Despite new European policies emphasizing its importance, the sector continues to decline. This study employs focus group methodology to examine the underlying causes of this decline from the perspective of shepherds. Two discussion groups were held with farmers from the regions of Castilla y León and Castilla-La Mancha in Spain, allowing us to contrast the testimonies of the practitioners with the existing literature. Our methodological approach emphasizes the value of focus groups in capturing complex socioeconomic dynamics within traditional livestock communities. The findings reveal multiple interconnected challenges: low profitability derived from legal requirements and concentration of demand; increasingly complex access to pastures due to local and state regulations; significant barriers to entry, including economic requirements and bureaucracy; difficulties in work-life balance; bureaucratic obstacles to positive externalities; conflictive relations with the tourism sector; weak associationism; and limited technology adoption. This study contributes to the methodological literature by demonstrating how focus groups can effectively reveal hidden dynamics in declining traditional sectors.